ANTIBACTERIAL AND PHYSICO-CHEMICAL STUDIES OF Cycas beddomei Dyer. MALE AND FEMALE CONES. - C. ALEKHYA,; N.YASODAMMA,; D.CHAITHRA., (International Journal of Pharma and Bio Sciences, 2013)
Cycas beddomei (Cycadaceae) is enlisted as Critically Endangered (C.E) under IUCN Status of Red listed Gymnosperm an endemic to Seshachalam Hill Ranges of Eastern ghats. The medicinal significance of Cycas male and female cones by the local herbalists leads to the phytochemical and antibacterial analysis. The main secondary metabolites in aqueous, alcoholic and methanolic extracts of male cones are alkaloids, flavonoids, phenols, terpenoids, steroids, tannins and glycosides; In female cones only terpenoids, steroids and glycosides are present. Antibacterial activity was observed on the selected four strains with 21.25mm to 27.75mm of Zone of Inhibition and 0.325mg to 2.5mg of Minimum Inhibitory Concentrations. It is proved that the therapeutic activity against the specific selected bacteria is equal to that of the herbal uses of C. beddomei male and female cones as aphrodisiac, skin diseases, mosquito repellent, general delibity, rheumatoid arthritis, wound healing, antidiabetic, antidiarrhoeal and tuberculosis. And also C. beddomei male and female cone crude drug is evaluated physicochemically to check its adulteration.